Malaysia's palm oil exports: does exchange rate overvaluation and undervaluation matters? - Mohd Sidek, Noor Zahirah; Yusoff, Mohammed; Mat Ghani, Gairuzazmi; Duasa, Jarita (Academic Journals, 2011)
This paper examines the impact of exchange rate risk on the exports of palm oil in the era of recurring financial crises and global economic instability. The exchange rate risk is captured by misalignments in the real bilateral US/RM exchange rate. This paper is divided into two parts. First, the incidence of exchange rate misalignment is observed using price-based approach (purchasing power parity) and model-based approach [behavioural equilibrium exchange rate (BEER)]. Next, the estimated exchange rate misalignment is used as a variable in the export model to capture the impact of risks. The long run estimates suggest that exchange rate misalignments affect palm oil exports in a negative manner. Then, the estimated misalignments are segregated into events of overvaluation and undervaluation to further comprehend their individual impact. Results suggest that in the long run, overvaluation has a significant negative impact on palm oil exports. The opposite however, could not be construed in the case of undervaluation which indicates asymmetries in the impact of overvaluation and undervaluation of the exchange rate on palm oil exports. Hence, it is imperative that policy-makers avoid both overvaluation and undervaluation and keep the real exchange rate in line with the economic fundamentals.